Analysis of Cisumdawu Toll Road Construction on the Development of Culinary Tourism Entrepreneurship in Sumedang Regency - Irena Novarlia; Vizra Aulia Sutanzani Saragih (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
The construction of the Cisumdawu toll road is an opportunity for the development of culinary tourism entrepreneurship in Sumedang Regency. The purpose of this research is as a further structuring step towards sustainable tourism that plays an important role in encouraging the development of culinary tourism entrepreneurship along with the construction of the Cisumdawu toll road access. The research used a qualitative descriptive method through a business canvas and SWOT analysis model. The results showed that the development of culinary tourism is currently concentrated near the Sumedang toll gate (50%) and out of 204 units that grow, develop, and continue only 173 units. The development of culinary tourism entrepreneurship through aggressive growth policies must be implemented with a focus on using strengths to take advantage of existing opportunities including aspects of marketing, operationalization, human resources, and finance in the hope of building tourism towards growth, development, and sustainability to support Sumedang as a Tourism Regency.